PENGEMBANGAN MODEL SISTEM PERSEDIAAN PERIODIC REVIEW DENGAN SATU EMERGENCY ORDER - Wiji Utomo, Sapto
This research develop a periodic review inventory model with two resupply policy, regular order and emergency order. Regular order will be placed on continuous basis in the end of review period, and emergency order will be placed on the closest time unit at the end of period. Regular order will be arrived after the deterministic lead time, hence emergency order has a shorter lead time than the regular. The lead time of emergency order is one time unit . This could mean that it will be arrived on one time unit or less. The emergency ordering cost is more expensive than the regular ordering cost. Due to the special transportation used to speed up the arrival such us by aircraft or special courier. This model is developed in the case of emergency ordering cost per unit is less than the penalty cost per unit . So far, the stock out is probably occuring along through the cycle time. The emergency order is more preferable than doing back order when stock out took place. The result of the numerical solutions proves that the periodic review inventory model with emergency ordering between the periodic review gives the better result by the lower expected total cost than the periodic review inventory model without employing emergency ordering